2017
DOI: 10.1093/toxsci/kfx230
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyphenol Chlorogenic Acid Protects Against Acetaminophen-Induced Hepatotoxicity by Activating ERK/Nrf2 Antioxidative Pathway

Abstract: Hepatotoxicity due to acetaminophen (APAP) overdose is a leading cause of drug-induced acute liver failure in clinic. Chlorogenic acid (CGA), a dietary polyphenol, was reported to prevent APAP-induced liver injury in our previous studies. This study aims to investigate the protection provided by CGA against APAP-induced hepatotoxicity via focusing on nuclear factor erythroid 2-related factor 2 (Nrf2) and extracellular regulated protein kinases (ERK)1/2. CGA prevented APAP-induced oxidative liver injury and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Serum ALT and AST levels are sensitive parameters of liver function [ 35 ]. In the current study, compared with the normal group, S180 tumor-bearing induced the significant elevation of serum ALT and AST levels (both P <0.01) ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum ALT and AST levels are sensitive parameters of liver function [ 35 ]. In the current study, compared with the normal group, S180 tumor-bearing induced the significant elevation of serum ALT and AST levels (both P <0.01) ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Serum ALT and AST are sensitive indicators of liver function and their obvious elevation commonly indicates liver toxicity [ 35 ]. In the present study, compared with the normal group, serum ALT and AST levels were significantly elevated in the control group of mice, indicating tumor-bearing induced liver damage, which was consistent with the results reported in many literatures [ 45 , 47–50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chlorogenic acid was reported to be a promising therapeutic agent for the detoxification of acetaminophen-induced hepatotoxicity. Wei et al reported that chlorogenic acid protects against APAP-induced hepatotoxicity by activating Nrf2 signaling pathway by blocking the binding of Nrf2 to its inhibitor protein, Keap1; furthermore, ERK1/2 has been reported to play a critical role in regulating chlorogenic acid-induced Nrf2 transcriptional activation [42]. There have been many report one the pleiotropic effect of polyphenol mixture and nutrients combination against various cancers including liver cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, green tea extract potentiated APAPinduced hepatotoxicity when applied after APAP treatment through causing glutathione depletion, indicating importance of the supplement interactions. Recently, Wei et al (2018) found that the natural polyphenol chlorogenic acid is protective against APAP-induced hepatotoxicity through activation of Nrf2 antioxidant signalling pathway by blocking the binding of Nrf2 to Keap1. In addition, ERK1/2 plays a critical role in regulation of the polyphenol chlorogenic acid-derived Nrf2 transcriptional activation.…”
Section: Camellia Sinensis (L) Kuntzementioning
confidence: 99%